Intérêt général, intérêt de classe, intérêt humain chez le jeune Marx - Stéphanie Roza (Astérion)
The article aims to question a commonplace : Marx would only have criticized the idea of “general interest” because, in his view, it would have been created during the French Revolution in order to guarantee and in the same time veil the bourgeois interest. The analysis, based on an enquiry on the German terms used by the young Marx, reveals, beside this critique, a theoretical attempt to think a “common” or “human” interest. This common interest would overcome class antagonism, and take over the interests of all and of everyone.